Korupsi dalam Perspektif Tasawuf Tahriki - M. Arrafie Abduh (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2008)
Dynamic Sufism (tasawuf tahriki in Arabic) develops positive thinking and realistic behavior about of paradigm of the material, spiritual and moral. Sufis are convinced anticorruption. Corruption in Indonesia especially has been in a virus, savage cancer and serious condition and its dangers are out of ordering state and civil society life in the fields of politics (money politics), economy (legal ling all ways obtain money and wealth) and law (manipulation of facts). Problem solving these phenomena, anticorruption movements have been done everywhere, either by an individual, the state or social organization, however, its result is not yet satisfactory. One of the effective methods (tariqah) according to dynamic Sufism perspective to solve corruption (fasad or risywah in al-Qur’an and tradition term), collusion and nepotism stressing corruption is a polytheism (syirik). It is a pity, corruption is not yet awarded or realized of one of polytheistic existence. In a polytheistic context necessary is interpreted by perspective of dynamic Sufism. Polytheism (syirik) indicate a long time public and environment corruption and humankind suffering. Corrupters must be heavily punished and psychotherapy in order to be cured of a psychological disease and moral hazard or immoral.